Implementation Of The Problem-Based Learning Model To Improve The Learning Outcomes Of Class III Students Of SD Negeri 104201 Desa Kolam Kec.Percut Sei Tuan Academic Year 2022-2023 - Ulfa Mayang Sari (JMEA : Journal of Mathematics Education and Application, 2023)
This type of research is class action research (Classroom Action Research), with the research subject being Grade III. A Student of SD Negeri 104201 Pond in the academic year 2022/2023. A total of 23 students, with details of 10 boys and 13 girls. The object of this research is the learning outcomes of students. This research was carried out in two learning cycles. 4 (are four) stages in each cycle, namely planning, implementation, observation/observation, and reflection. The data collection tools are tests, observation sheets, and documentation. The results of data analysis from 23 students obtained classical completeness in the teacher's initial observation before using the Problem Based Learning (PBL) learning model, namely 13%. The acquisition of cycle I significantly increased with 52% classical completeness and was followed up in cycle II with 87% classical completeness.